Review Article about EMG Monitoring System - Jawad, Fadhil Kadhim; Muhammad, Murtada Qahtan; Salman, Esraa Mohammed; Saber, Shanaz Sirwan Fakhri (American Journal of Botany and Bioengineering, 2025)
Electromyography (EMG) monitoring systems play a critical role in diagnosing neuromuscular disorders and enhancing rehabilitation and muscle-controlled applications. However, challenges such as signal accuracy, cost, and integration with modern technologies remain significant barriers to widespread adoption. This study presents an Arduino-based EMG monitoring system utilizing the AD8226 amplifier to measure and analyze muscle activity. The methodology involves interfacing EMG sensors with an Arduino UNO to capture electrical signals from muscle contractions and display the results in real time. Findings indicate that the system provides reliable muscle signal detection, offering a cost-effective and portable alternative to traditional EMG systems. These results highlight the potential of integrating EMG monitoring with wearable technology and IoT for remote healthcare applications, improving accessibility and efficiency in neuromuscular diagnostics and rehabilitation.